UNDERSTANDING PEACE STUDIES AS PART OF INTERNATIONAL RELATIONS - M. Prakoso Aji; Jerry Indrawan (Indonesia Defense University, 2019)
Peace Studies is a discipline that is derived from International Relations. With the development of International Relations, they are dealing with cases related to conflicts and wars between states, as well as states with non-states. For this reason, Peace Studies was born so that it can focus on discussing issues surrounding conflict, war, and resolution efforts. Peace Studies in general are associated with the concept of conflict resolution. One method of conflict resolution in Peace Studies is the concept of conflict transformation. Conflict transformation is not only aimed at stopping conflict and to change patterns of negative relations between conflicting parties, but also to change the political, social and economic structure that causes the patterns of negative relations. Peace Studies offers a new analysis of how International Relations should look at the complexity of relations between actors. The author did not conduct field research related to this article, but conduct a conceptual research through literature study. The purpose of this article is to see how Peace Studies can help answer problems in International Relations related to conflicts or wars that occur internationally.Keywords: peace studies, conflict, armed conflict, violence, and conflict transformation